2003
DOI: 10.21273/horttech.13.4.0605
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching Potential under Variable and Uniform Nitrogen Fertilizer Management in Irrigated Potato Systems

Abstract: Potato (Solanum tuberosum) production in Washington State's Central Columbia Plateau faces nitrogen (N) management challenges due to the combination of coarse textured soils (sandy loam to loam) and hilly topography in this region as well as the high N requirement of potato. Potato growth and development can vary with the N availability across the field. In this 2-year study, two adjacent potato fields were selected each year (1999 and 2000). Each field was soil sampled on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…There are few published reports for variable management of potatoes in landform-based management zones. Whitley and Davenport (2003) found that variable management of N fertilizer in potatoes based on spatial variability of soil organic matter reduced N leaching potential during the early part of the growing season, though this effect did not persist during the entire growing season. Cambouris et al (2008) assessed variable management based on two management zones, for rate and timing of N fertilizer application on potato tuber yield, distribution and specific gravity.…”
Section: Discussionmentioning
confidence: 96%
“…There are few published reports for variable management of potatoes in landform-based management zones. Whitley and Davenport (2003) found that variable management of N fertilizer in potatoes based on spatial variability of soil organic matter reduced N leaching potential during the early part of the growing season, though this effect did not persist during the entire growing season. Cambouris et al (2008) assessed variable management based on two management zones, for rate and timing of N fertilizer application on potato tuber yield, distribution and specific gravity.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is critical to manage N using site specific nutrient management (SSNM) system, which accounts for spatial soil variability within the fields and makes precise recommendation of N need that increases efficiency of applied N (Khosla et al 2002;Cambouris et al 2008). Site-specific N management has reduced NO 3 leaching on areas with high leaching potential on loamy fine sandy soil of Washington, indicating SSNM's potential to improve N management in potato cropping system (Whitley et al 2001). This can be done either by dividing fields into management zones which differ in term of soil properties, landscape position, and yield potential or using optical methods to assess spatial variation in crop and soil N status.…”
Section: Site-specific Nitrogen Management (Ssnm) and Precision Agricmentioning
confidence: 99%
“…These measures of "real-time" crop N status can be linked directly to variable rate fertilizer N applicators, which can immediately translate the measurements into fertilizer rates, and tailor N management to the precise need of the crop for a specific field at real time. Variable fertilizer N application method can reduce N loss (Whitley and Davenport 2003). This practice is common in Europe for cereal crops (Zillmann et al 2006;Jorgensen and Jorgensen 2007), but has not been fully developed for potatoes.…”
Section: Site-specific Nitrogen Management (Ssnm) and Precision Agricmentioning
confidence: 99%
“…After delineation of management zones relationships between spatial variation in soil/crop parameters and yield can be examined (Pilesjö et al, 2005). Positive results were found by researchers after dividing the fields into management zones depending on topographic features and other soil variation in different cropping systems (Thrikawala et al, 1999;Whitley and Davenport, 2003;Goddard and Grant, 2001).…”
Section: Management Zones Can Be Delineated Based On the Distributionmentioning
confidence: 99%